Budi Tani Sebagai Ekspresi Ritual Dan Pertunjukan Di Desa Lencoh Kecamatan Sela Kabupaten Boyolali - Dwi Rahmani (Institut Seni Indonesia Surakarta, 2009)
Budi Tani Dance performance was grown and developed at Lencoh Village Society as part of syawalan traditional ceremony that conducted on village cleaning day (bersih dusun ). This ceremony was related its advocates’sociocultural. For Lencoh Village Society, its existence is syncretism that seen through ceremonial activities. By provided offerings and followed Budi Tani Dance performance full of symbols, Lencoh society was attempted to communicate with powerful beings for made dual relationship such as vertically and horizontally. Lencoh society was communicated with its God, ancestors and holy soul to get safety, benediction in its life through vertically relationship. Then, togetherness and devotion sense based on cooperation and assistance each others would built through horizontally relationship. Traditional ceremony of syawalan that conducted on cleaning day (bersih dusun) and followed by Budi Tani Dance performance with magical religious attitude related to norm and social attitude to preserve Lencoh society life as the prop was executed based on belief.Keyword : Folk Dance, Budi Tani Dance